2014
DOI: 10.1021/jm401838x
|View full text |Cite
|
Sign up to set email alerts
|

Simplified 2-Aminoquinoline-Based Scaffold for Potent and Selective Neuronal Nitric Oxide Synthase Inhibition

Abstract: Since high levels of nitric oxide (NO) are implicated in neurodegenerative disorders, inhibition of the neuronal isoform of nitric oxide synthase (nNOS) and reduction of NO levels are therapeutically desirable. Nonetheless, many nNOS inhibitors mimic l-arginine and are poorly bioavailable. 2-Aminoquinoline-based scaffolds were designed with the hope that they could (a) mimic aminopyridines as potent, isoform-selective arginine isosteres and (b) possess chemical properties more conducive to oral bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 70 publications
5
58
0
Order By: Relevance
“…The inhibitor K S values, determined from an imidazole displacement assay are reported in µM for each inhibitor of bsNOS. Isolation and characterization of NOS inhibitors marked by α were previously reported in (Delker et al, 2010), β in (Huang et al, 2013), γ in (Huang et al, 2014), δ in (Holden et al, 2013), ξ in (Jing et al, 2014), π in (Holden et al, 2013), σ in (Huang et al, 2012), φ in (Huang et al, 2014), ψ (Holden et al, 2014), ϑ in (Cinelli et al, 2014), ϕ in (Kang et al, 2015, unpublished data), and θ reported here.…”
Section: Figuresupporting
confidence: 57%
See 1 more Smart Citation
“…The inhibitor K S values, determined from an imidazole displacement assay are reported in µM for each inhibitor of bsNOS. Isolation and characterization of NOS inhibitors marked by α were previously reported in (Delker et al, 2010), β in (Huang et al, 2013), γ in (Huang et al, 2014), δ in (Holden et al, 2013), ξ in (Jing et al, 2014), π in (Holden et al, 2013), σ in (Huang et al, 2012), φ in (Huang et al, 2014), ψ (Holden et al, 2014), ϑ in (Cinelli et al, 2014), ϕ in (Kang et al, 2015, unpublished data), and θ reported here.…”
Section: Figuresupporting
confidence: 57%
“…Despite slight differences in binding of the fluorinated-benzyl group, in both NOS isoforms binding of 19 and 32 was further stabilized by H-bonds between the secondary amine of each inhibitor and the heme propionate groups (Figures 3D and 3E). Direct comparison of the bsNOS- 19 and the previously reported nNOS- 19 (Cinelli et al, 2014) structures revealed the binding mode of 19 to be unchanged between the two NOS isoforms. However, the binding mode in bsNOS was further stabilized by the hydrophobic contact between Ile-218 and the aminoquinoline group of 19 .…”
Section: Resultsmentioning
confidence: 79%
“…It is known that contact between the halophenyl rings of 1 and 2 and the hydrophobic pocket residues Tyr706, Leu337, and Met336 improves potency and n/e selectivity. 18 What is responsible for the n/e selectivity for these compounds lacking obvious hydrophobic contact? X-ray crystallography indicates that in eNOS, a common binding mode is observed for most phenyl ether-linked aminoquinolines, characterized by an “upward” position of the ether bond, where the phenyl ring sits perpendicular to the plane of the aminoquinoline.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, 7-substituted-2-aminoquinolines were prepared via readily accessible chloroquinoline 23 18, 29 (Scheme 1) by performing a Korodi amidation 30 to produce 2-acetamidoquinoline 25 . Unfortunately, this procedure gives irreproducible yields and is not readily amenable to scale-up.…”
Section: Chemistrymentioning
confidence: 99%
“…Moreover, the fact that we have been able to identify nitro-guanidines which are selective for nNOS or eNOS suggests that these may be useful for pathological conditions where suppressing these isoforms of NOS may be beneficial. Other workers are pursuing selective nNOS inhibitors for therapeutic intervention in neuromuscular disorders [12] and neurodegenerative disease such as Alzheimer’s and Parkinson’s disease. [13,14] A number of those known inhibitors are analogs of the substrate L-arginine and include, in particular N ω -nitro-arginine.…”
Section: Introductionmentioning
confidence: 99%